Comparison between conventional and modern methods for extraction of Rosmarinus officinalis leaves - Mutalib, Lana Yousif (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: The first step in the process of drug obtaining from natural origin was standardized extraction procedure. The aim of the study was to compare extracts of Rosemarinusofficinalis obtained by different methods of extraction from mass and phytochemical points. Methods: Comparison was done through measuring the mass of yield of Rosmarinusofficinalis extracts using different methods of extraction. Qualitative analysiswas done through preliminary phytochemical screening tests for the presence of secondary natural groups of extracts of rosemary plant obtained by different methods of extraction. Results: The highest yield mass (7.666%) was obtained from the microwave assisted extraction method belong to the modern methods of extraction group. In qualitative analysis, there was no difference in the presence of the secondary natural product groups with different methods of extraction belonging to the two classes conventional and modern. New group of natural products were detected in the ethanolic plant extract are condensed tannin and quinone. Conclusion: Microwave assisted extraction is considered as the most efficient method of extraction from quantitative measures. Qualitative analysis of ethanolic extract of Rosmarinusofficinalis shows presence of phytochemical compounds like condensed tannin, quinon, flavonoid, terpenoid and phenols.